2022
DOI: 10.5267/j.uscm.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Building green supply chain management in pharmaceutical companies in Indonesia

Abstract: This study aims to analyze the contribution of Green Manufacturing and Green Distribution on improving the performance of Green Supply Chain Management (GSCM) through Reverse Logistics. The development of industry and increasing consumer concern for the environment as well as issues regarding the concept of an environmentally sound industry have forced industries to adjust in line with the GSCM concept. To make the program a success, Green Manufacturing, Green Distribution, and Reverse Logistics are assumed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For example, Yusup et al (2015) discovered that while Malaysia has made some progress toward sustainable manufacturing practices, greater awareness among businesses about the benefits of such practices is needed. Similarly, a study from Indonesia discovered that while Indonesia has implemented a variety of policies aimed at encouraging sustainable manufacturing practices, these policies have not been effectively enforced (Ricardianto et al , 2022). In the Thai manufacturing sector, Piyathanavong et al (2019) reported existing barriers to the adoption of production sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yusup et al (2015) discovered that while Malaysia has made some progress toward sustainable manufacturing practices, greater awareness among businesses about the benefits of such practices is needed. Similarly, a study from Indonesia discovered that while Indonesia has implemented a variety of policies aimed at encouraging sustainable manufacturing practices, these policies have not been effectively enforced (Ricardianto et al , 2022). In the Thai manufacturing sector, Piyathanavong et al (2019) reported existing barriers to the adoption of production sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Supply Chain is a network of all organizations and activities related to the flow and transformation of goods, information, and money (Hidayati & Hasibuan, 2019). Supply chain management is a method or approach to manage the flow of products, information and money in an integrated manner by involving parties from upstream to downstream consisting of suppliers, companies, distribution actors and consumers (Ricardianto et al, 2022a). Activities in supply chain management include product development, procurement of materials and components of a product, production planning, inventory control, distribution and product returns (Ricardianto et al, 2022b).…”
Section: Supply Chain Managementmentioning
confidence: 99%
“…Ref. [27] focused on establishing GSCM in pharmaceutical companies in Indonesia, and Ref. [28] examined factors influencing managers' intention to adopt GSCM practices in manufacturing firms in Jordan.…”
Section: Introductionmentioning
confidence: 99%